Magnetic resonance force microscopy and a single-spin measurement - Berman, Gennady P., 1946- (World Scientific, 2006)
Magnetic resonance force microscopy (MRFM) is a rapidly evolving field which originated in 1990s and matured recently with the first detection of a single electron spin below the surface of a non-transparent solid. Further development of MRFM techniques will have a great impact on many areas of science and technology including physics, chemistry, biology, and even medicine. Scientists, engineers, and students from various backgrounds will all be interested in this promising field. The objective of this "multi-level" book is to describe the basic principles, applications, and the advanced theor.